Variasi Bahasa dalam Instagram pada Akun Arief Muhammad (@armuh) Kajian Sosiolinguistik - Ningtyas, Ajeng Setia; Suharyo, Suharyo (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2023)
Language variations have many types and variations, one of which is the Martin Joos model of formality. The formal variety of the Martin Joos model discusses the five formal levels of a language, namely frozen variety, formal variety, consultative variety, casual variety, and intimate variety. The purpose of this study is to describe Arief Muhammad's use of various languages with his followers which are reviewed through sociolinguistic studies using Martin Joos' theory. This study used a purposive sampling technique to collect data and used non-participant observation and documentation (screenshots). Then the data were analyzed using a qualitative descriptive method with the Martin Joos model of formality theory. From the research data obtained from Arief Muhammad's caption, there are three kinds of languages, namely consultative languages, casual languages and intimate languages. The same thing can be seen from the research data obtained from the comments column, there are three kinds of language, namely the variety of consultative language, the variety of casual language and the variety of intimate languages.